2014
DOI: 10.3892/mco.2014.336
|View full text |Cite
|
Sign up to set email alerts
|

XAGE-1b expression is associated with the diagnosis and early recurrence of hepatocellular carcinoma

Abstract: Abstract. XAGE-1b is a 470 bp transcript of the XAGE-1 gene, which belongs to the cancer-testis antigens that exhibit a restricted pattern of expression in normal tissues. Recently, the expression of XAGE-1b has been shown to be frequent in patients with hepatocellular carcinoma (HCC). However, the underlying mechanism is not fully understood. To investigate the role of XAGE-1b in HCC diagnosis and postoperative evaluation, the expression level of XAGE-1b was first examined in the tissue and peripheral blood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The current study found that XAGE1-positive ovarian cancer patients had considerably greater levels of XAGE1 gene expression than benign tumor patients, indicating that the XAGE1 gene has a high specificity as a diagnostic marker for distinguishing malignant from benign ovarian cancer. Our findings were consistent with a recent study that found elevation of XAGE 1b mRNA expression in 64.4 percent of hepatocellular carcinoma tissue samples, but not in any benign liver tumors [ 21 ]. Gjerstorff et al discovered significant levels of expression of numerous cancer-testis antigens (CTAs) in Tumorigenicity human mesenchymal stem cells, including XAGE-1 [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current study found that XAGE1-positive ovarian cancer patients had considerably greater levels of XAGE1 gene expression than benign tumor patients, indicating that the XAGE1 gene has a high specificity as a diagnostic marker for distinguishing malignant from benign ovarian cancer. Our findings were consistent with a recent study that found elevation of XAGE 1b mRNA expression in 64.4 percent of hepatocellular carcinoma tissue samples, but not in any benign liver tumors [ 21 ]. Gjerstorff et al discovered significant levels of expression of numerous cancer-testis antigens (CTAs) in Tumorigenicity human mesenchymal stem cells, including XAGE-1 [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…The statistically significant difference in expression levels in connection to stage III has been shown compared with stage I. Similar results were found in earlier research, including Pan et al , who reported that XAGE 1b mRNA levels were raised in patients with hepatocellular carcinoma with higher stages of tumor node metastasis [II~IV][ 21 ]. Men et al have discovered the pulmonary metastatic capacity of XAGE-1b in nude mice [ 28 ], but no association between CT expression and clinical variables like tumor history and histology has been observed in lung cancer patients [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…The expression of the CTA family XAGE-1b is significantly higher in liver cancer tissues and peripheral blood than in a non-liver cancer group. Because the expression level of XAGE-1b is closely associated with the 1-year recurrence rate of patients 27 , it can be useful for early diagnosis and prognosis. The expression levels of the CTA family members MAGE-3 and MAGE-4 mRNA are significantly higher in the peripheral blood of metastatic hepatocellular carcinoma patients than in a non-metastasis group, and they can be used to determine whether hepatoma cells undergo blood vessel metastasis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…XAGE-1b is considered as a tumor serological marker which assisted clinical diagnosis [7,14] . Moreover, signi cant dysregulated levels of XAGE-1b were observed in several tumors [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]21] . However, XAGE-1b expression in GC and its role in the prognosis of GC patients remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…XAGE-1b is characterized as wide expression spectrum, high expression rate and strong immunogenicity, which also leads to a variety of transcription variations. It has been reported that XAGE-1b was highly expressed in melanoma [5,6] , lung cancer [7][8][9][10][11][12][13] , prostate cancer [14,15] and hepatocellular carcinoma [16,17] , and was correlated with the tumor poor prognosis.…”
Section: Introductionmentioning
confidence: 99%